Pemetrexed in patients with refractory soft tissue sarcoma: a non-comparative multicenter phase II study of the German Sarcoma Group AIO-STS 005 - Hartmann, Jörg Thomas; Egerer, Gerlinde (Investigational new drugs, 2013)
Background This study evaluated efficacy and safety of pemetrexed in patients with refractory soft tissue sarcoma. Methods Patients received pemetrexed intravenously at a dose of 500 mg/m² every 21 days until progression or unacceptable toxicity. The primary endpoint was objective tumor response. Results Fourty-eight of 53 screened patients were included and received a total of 200 cycles (median 2; range 1-30). Median age was 53 years (range, 20-81). The observed toxicity profile was favorable. NCI-CTC hematologic grade 3/4 toxicity consisted of neutropenia in 13 %, anemia in 15 %, and febrile neutropenia in 4 % of patients of patients, respectively. Non-hematologic CTC grade 3/4 toxicity consisted of elevated ASAT/ALAT in 10 %, hyperglycemia in 6 %, infection with or without neutropenia in 6 %, nausea in 2 % and stomatitis in 2 % of patients. No other grade 3 toxicities and no treatment-related toxic deaths were observed. Overall response as defined by RECIST was 5 %, 16 patients experienced stable disease (40 %). The estimated 3- and 6-months progression-free rates were 33.3 % and 14.6 %, respectively. Conclusions In patients with refractory STS, pemetrexed is well tolerated and moderately effective. The confirmed objective response rate in STS is low, however, disease stabilizations are seen in a high proportion of patients (ClinicalTrials.gov NCT00427466).
Published online: 5 July 2012
Gesehen am 08.10.2021